Determinants and underlying causes of frequent attendance in midwife-led care: an exploratory cross-sectional study - Janneke T. Gitsels - van der Wal; Lisanne A. Gitsels; Angelo Hooker; Britte van Weert; Linda Martin; Esther I. Feijen - de Jong (BMC, 2019)
Abstract Background An adequate number of prenatal consultations is beneficial to the health of the mother and fetus. Guidelines recommend an average of 5-14 consultations. Daily practice, however, shows that some women attend the midwifery practice more frequently. This study examined factors associated with frequent attendance in midwifery-led care. Methods We conducted a cross-sectional study in a large midwifery practice in the Netherlands among low-risk women who started prenatal care in 2015 and 2016. Based on Andersen's behavioral model, we collected data on potential determinants from the digital midwifery's practice database. Prenatal healthcare utilization was measured by a revised version of the Kotelchuck Index, which measures a combination of care entry and numbers of visits. Logistic regression models were fitted to estimate the likelihood of frequent attendance compared to the recommended number of visits, adjusted for all relevant factors. Separate models were fitted on the non-referred and the referred group of obstetric-led care, as referral was found to be an effect modifier. Results The prevalence of frequent attendance was 23% (243/1053), mainly caused by worries and/or vague complaints (44%; 106/243). Among non-referred women, 53% (560/1053), frequent attendance was associated with consultation with an obstetrician (OR = 3.99 (2.35-6.77)) and exposure to sexual violence (OR = 2.17 (1.11-4.24)). Among the referred participants, 47% (493/1053), frequent attendance was associated with a consultation with an obstetrician (OR = 2.75 (1.66-4.57)), psychosocial problems in the past or present (OR = 1.85 (1.02-3.35) or OR = 2.99 (1.43-6.25)), overweight (OR = 1.88 (1.09-3.24)), and deprived area (OR = 0.50 (0.27-0.92)). Conclusion Our exploratory study indicates that the determinants of frequent attendance in midwifery-led care differs between non-referred and referred women. Underlying causes for frequent attendance was mainly because of non-medical reasons. Implication for practice: A trustful midwife-client relationship is known to be needed for clients such as frequent attenders to share more detailed, personal stories in case of vague complaints or worries, which is necessary to identify their implicit needs.